Progeny array analysis to estimate outcrossing rates, inbreeding coefficients, and inbreeding depression among native, naturalized, and invasive populations of Mimulus guttatus (Phrymaceae) - Dudash, Michele R.; Berg, Jason A.; Zimmer, Elizabeth A. (Frontiers in Plant Science, 2024)
colonizing success following introduction into locations outside of the native distribution.For plant species capable of mixed-mating, both selfing and outcrossing can be advantageous and promote the establishment, persistence, and spread of newly arrived populations. To investigate how mating systems may contribute to the invasion process we estimated mating system parameters in perennial populations of the model plant species, Mimulus guttatus from its native range (West coast USA), non-native populations that are established but have not become invasive (East coast USA, >50 years), and populations in invasive regions (UK >200 years). Studies that include mating system data across the continuum of the invasion process are rare, thus here we utilize molecular markers to estimate outcrossing rates (t), inbreeding coefficients (F), and inbreeding depression in native, naturalized, and invasive populations. Overall, we found support for stable the persistence of mixed-mating across populations independent of their location, variability in the relationship between outcrossing rates and inbreeding depression across populations, and evidence, for the bridgehead process, where non-native populations are may be the sources for the further establishment or reinforcement of additional nonnative populations. The methodology we deployed had its own assumptions, and sampling design constraints, and biases that contributed to the variation in the parameter estimates.All M. guttatus populations likely rely on selfing through both within clone, and within flower and plant mating in addition to vegetative propagation. and The results underscore